The Evolution of Prosocial and Antisocial Competitive Behavior and the Emergence of Prosocial and Antisocial Leadership Styles - Paul Gilbert; Jaskaran Basran (Frontiers in Psychology, 2019)
Evolutionary analysis focuses on how genes build organisms with different strategies for engaging and solving life’s challenges of survival and reproduction. One of those challenges is competing with conspecifics for limited resources including reproductive opportunities. This article suggests that there is now good evidence for considering two dimensions of social competition. The first, has been labeled as antisocial strategies, to the extent that they tend to be self-focused, threat sensitive and aggressive, and use tactics of bulling, threatening, and intimidating subordinates, or even injuring/killing competitors. Such strategies can inhibit care and affiliative social interactions and motivation. The social signals emitted stimulate threat processing in recipients and can create stressed and highly stratified groups with a range of detrimental psychological and physiological effects. Second, in contrast, prosocial strategies seek to create relaxed and secure social interactions that enable sharing, cooperative, mutually supportive and beneficial relationships. The friendly and low/no threat social signals emitted in friendly cooperative and affiliative relationships stimulate physiological systems (e.g., oxytocin, the vagus nerve of the parasympathetic system) that downregulates threat processing, enhances the immune system, and facilitates frontal cortical processes and general wellbeing. This article reviews the literature pertaining to the evidence for these two dimensions of social engagement.